Curable resin composition, coating layer, and film

By using a curable resin with two or more glyceraldehyde groups and a coupling agent with one glyceraldehyde group, combined with a photocuring primary agent and UV-LED irradiation, the problem of the existing hard coating agent degradation in high temperature and high humidity environments is solved, and excellent hardness and adhesion in such environments are achieved.

JP7667918B2Active Publication Date: 2025-04-23SEKISUI CHEMICAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024549488
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-04-24
Filing Date
2024-04-23
Publication Date
2025-04-23
Estimated Expiration
2044-04-23

AI Technical Summary

Technical Problem

It is difficult for existing hard coating agents to maintain hardness and adhesion in high temperature and high humidity environments, especially adhesion to glass.

Method used

A curable resin composition is used, which comprises a curable resin having two or more glyceraldehyde groups, a coupling agent having one glyceraldehyde group and a photocuring primary agent, and illumination of 365 nm wavelength and 100 mW/cm² under UV-LED irradiation.

Benefits of technology

In high temperature and high humidity environments, the cured resin composition can maintain excellent hardness and adhesion, especially adhesion to glass, and is suitable for protecting and sealing optical semiconductor devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007667918000001
    Figure 0007667918000001
Patent Text Reader

Abstract

One purpose of the present invention is to provide a curable resin composition able to yield a cured product having excellent hardness and adhesive properties even if exposed to a high temperature high humidity environment. Another purpose of the present invention is to provide a coating layer and a film that are formed using said curable resin composition. The present invention is a curable resin composition which contains a curable resin, a coupling agent and a polymerization initiator. The curable resin includes a curable resin having two or more glycidyl groups per molecule. The coupling agent includes a coupling agent having one glycidyl group per molecule. Relative to a total of 100 parts by mass of the curable resin as a whole and the coupling agent as a whole, the content of the coupling agent having one glycidyl group per molecule is 10-50 parts by mass.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a curable resin composition. The present invention also relates to a coating layer and a film formed using the curable resin composition. [Background technology]

[0002] Optical semiconductor elements such as LEDs are widely used in backlights of liquid crystal displays, lighting fixtures, etc., due to their low power consumption and long life. Optical semiconductor elements deteriorate when exposed to moisture or gas in the atmosphere, and the light extraction efficiency decreases, so they are usually sealed with a sealant and protected with a cover glass or the like before use. In recent years, as a method for protecting and sealing optical semiconductor elements without using a cover glass or the like, forming a coating layer on the surface of an optical semiconductor element using a hard coat agent has been considered (for example, Patent Document 1, etc.). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2016-1657 A Summary of the Invention [Problem to be solved by the invention]

[0004] A hard coating agent for protecting and sealing an optical semiconductor element is required to have both hardness and adhesiveness (particularly adhesiveness to glass) after curing. However, even if a conventional hard coating agent has excellent hardness and adhesiveness after curing, it is difficult to maintain the hardness and adhesiveness when exposed to a high-temperature and high-humidity environment. The present invention aims to provide a curable resin composition that can give a cured product having excellent hardness and adhesion even when exposed to a high-temperature and high-humidity environment, and a coating layer and a film formed using the curable resin composition. [Means for solving the problem]

[0005] Disclosure 1 is a curable resin composition comprising a curable resin, a coupling agent, and a polymerization initiator, wherein the curable resin comprises a curable resin having two or more glycidyl groups in one molecule, the coupling agent comprises a coupling agent having one glycidyl group in one molecule, and the content of the coupling agent having one glycidyl group in one molecule is 10 parts by mass or more and 50 parts by mass or less relative to a total of 100 parts by mass of the entire curable resin and the entire coupling agent. Disclosure 2 is the curable resin composition of Disclosure 1, wherein the polymerization initiator includes a photopolymerization initiator. Disclosure 3 is a method for curing the above-mentioned curable resin composition using a UV-LED at a wavelength of 365 nm and an illuminance of 100 mW / cm 2 The curable resin composition according to Disclosure 1 or 2 is a curable resin composition according to Disclosure 1 or 2, which is irradiated with ultraviolet light for 30 seconds, and then heated at 100°C for 30 minutes, and the cured product obtained is subjected to a reliability test in which the product is exposed to an environment of 85°C and 85% RH for 24 hours, and then has a pencil hardness of 4H or more as measured in accordance with JIS K 5600-5-4. Disclosure 4 is a method for curing the above-mentioned curable resin composition using a UV-LED at a wavelength of 365 nm and an illuminance of 100 mW / cm 2 The curable resin composition of Disclosure 1, 2, or 3 is irradiated with ultraviolet light for 30 seconds, followed by heating at 100°C for 30 minutes, and the cured product obtained is subjected to a reliability test in which the product is exposed to an environment of 85°C and 85% RH for 24 hours. After that, the cured product is classified as 0 or 1 in an adhesion test by a cross-cut method in accordance with JIS K 5600-5-6. The present disclosure 5 is a coating layer formed using the curable resin composition of the present disclosure 1, 2, 3 or 4. The present disclosure 6 is a film formed using the curable resin composition of the present disclosure 1, 2, 3 or 4. The present invention will be described in detail below.

[0006] The present inventors have studied the use of a curable resin composition in combination with a curable resin having two or more glycidyl groups per molecule and a coupling agent having one glycidyl group per molecule, and have set the content of the coupling agent having one glycidyl group per molecule within a specific range. As a result, they have found that a curable resin composition can be obtained that can give a cured product having excellent hardness and adhesiveness (especially adhesiveness to glass) even when exposed to a high-temperature and high-humidity environment, and have completed the present invention.

[0007] The curable resin composition of the present invention contains a curable resin. The above-mentioned curable resin includes a curable resin having two or more glycidyl groups in one molecule (hereinafter, also referred to as "curable resin according to the present invention"). By using the curable resin of the present invention in combination with a coupling agent having one glycidyl group per molecule in a content described below, the curable resin composition of the present invention can give a cured product that has excellent hardness and adhesion (particularly adhesion to glass) even when exposed to a high-temperature, high-humidity environment.

[0008] The curable resin according to the present invention has two or more glycidyl groups in one molecule. From the viewpoint of reactivity and hardness of the obtained cured product, the curable resin according to the present invention more preferably has four or more glycidyl groups in one molecule. In addition, the number of glycidyl groups in the curable resin according to the present invention is not particularly limited, but the practical upper limit is eight.

[0009] Specific examples of the curable resin according to the present invention include dicyclopentadiene dimethanol diglycidyl ether, trimethylolpropane triglycidyl ether, ethylene oxide-added trimethylolpropane triglycidyl ether, propylene oxide-added trimethylolpropane triglycidyl ether, caprolactone-modified trimethylolpropane triglycidyl ether, glycerin triglycidyl ether, propylene oxide-added glycerin triglycidyl ether, pentaerythritol triglycidyl ether, ditrimethylolpropane tetraglycidyl ether, pentaerythritol tetraglycidyl ether, dipentaerythritol pentaglycidyl ether, and dipentaerythritol hexaglycidyl ether.

[0010] The above curable resins may be used alone or in combination of two or more kinds.

[0011] The preferred lower limit of the content of the curable resin according to the present invention relative to 100 parts by mass of the total of the entire curable resin and the coupling agent is 50 parts by mass. When the content of the curable resin according to the present invention is 50 parts by mass or more, the cured product of the obtained curable resin composition has excellent hardness and adhesion (particularly adhesion to glass) when exposed to a high-temperature and high-humidity environment. The preferred lower limit of the content of the curable resin according to the present invention in the entire curable resin is 50 mass%, and the more preferred lower limit is 90 mass%. The content of the curable resin according to the present invention in the entire curable resin may be 100 mass%, that is, the curable resin may consist only of the curable resin according to the present invention.

[0012] The preferred lower limit of the total content of the curable resin in 100 parts by mass of the curable resin composition of the present invention is 40 parts by mass, and the preferred upper limit is 90 parts by mass. When the total content of the curable resin is within this range, the obtained curable resin composition has better curability and adhesiveness. The more preferred lower limit of the total content of the curable resin is 45 parts by mass, and the more preferred upper limit is 85 parts by mass.

[0013] The curable resin composition of the present invention contains a coupling agent. The above coupling agent includes a coupling agent having one glycidyl group in one molecule (hereinafter also referred to as "the coupling agent according to the present invention"). In this specification, the above-mentioned "having one glycidyl group in one molecule" means having only one glycidyl group in one molecule, and a coupling agent having two or more glycidyl groups in one molecule is not regarded as a coupling agent according to the present invention.

[0014] The coupling agent according to the present invention is preferably a silane coupling agent having one glycidyl group in one molecule.

[0015] Specific examples of the silane coupling agent having one glycidyl group per molecule include 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 3-glycidoxypropyltriethoxysilane.

[0016] The above coupling agents may be used alone or in combination of two or more kinds.

[0017] The lower limit of the content of the coupling agent according to the present invention relative to the total of the curable resin and the coupling agent, 100 parts by mass, is 10 parts by mass, and the upper limit is 50 parts by mass. When the content of the coupling agent according to the present invention is 10 parts by mass or more, the cured product of the obtained curable resin composition has excellent adhesion when exposed to a high-temperature and high-humidity environment. When the content of the coupling agent according to the present invention is 50 parts by mass or less, the cured product of the obtained curable resin composition has excellent hardness when exposed to a high-temperature and high-humidity environment. The preferred lower limit of the content of the coupling agent according to the present invention is 20 parts by mass, the preferred upper limit is 40 parts by mass, and the more preferred upper limit is 30 parts by mass. The lower limit of the content of the coupling agent according to the present invention in the entire coupling agent is preferably 10% by mass, more preferably 30% by mass. The content of the coupling agent according to the present invention in the entire coupling agent may be 100% by mass, that is, the coupling agent may consist of only the coupling agent according to the present invention.

[0018] The curable resin composition of the present invention contains a polymerization initiator. The polymerization initiator preferably includes a photopolymerization initiator. The photopolymerization initiator preferably includes a cationic photopolymerization initiator. The photocationic polymerization initiator is not particularly limited as long as it generates a protonic acid or a Lewis acid upon irradiation with light, and may be an ionic photoacid generating type or a nonionic photoacid generating type.

[0019] The anion portion of the ionic photoacid generating cationic photopolymerization initiator is, for example, BF4 - , PF6 - , SbF6 - , (BX4) - (wherein X represents a phenyl group substituted with at least two fluorine or trifluoromethyl groups). The anion moiety may be PF m (C n F 2n+1 ) 6-m - (wherein, m is an integer of 0 or more and 5 or less, and n is an integer of 1 or more and 6 or less). Examples of the ionic photoacid generating type photocationic polymerization initiator include aromatic sulfonium salts, aromatic iodonium salts, aromatic diazonium salts, aromatic ammonium salts, (2,4-cyclopentadiene-1-yl)((1-methylethyl)benzene)-Fe salts, and the like, each of which has the anion moiety.

[0020] Examples of the aromatic sulfonium salt include bis(4-(diphenylsulfonio)phenyl)sulfide bishexafluorophosphate, bis(4-(diphenylsulfonio)phenyl)sulfide bishexafluoroantimonate, bis(4-(diphenylsulfonio)phenyl)sulfide bistetrafluoroborate, bis(4-(diphenylsulfonio)phenyl)sulfide tetrakis(pentafluorophenyl)borate, diphenyl-4-(phenylthio)phenylsulfonium hexafluorophosphate, diphenyl-4-(phenylthio)phenylsulfonium tris(pentafluoroethyl)trifluorophosphate, diphenyl-4-(phenylthio)phenylsulfonium hexafluoroantimonate, diphenyl-4-(phenylthio)phenylsulfonium tetrafluoroborate, and diphenyl-4-(phenylthio)phenylsulfonium tetrakis(pentafluorophenyl)borate. , triphenylsulfonium hexafluorophosphate, triphenylsulfonium hexafluoroantimonate, triphenylsulfonium tetrafluoroborate, triphenylsulfonium tetrakis(pentafluorophenyl)borate, bis(4-(di(4-(2-hydroxyethoxy))phenylsulfonio)phenyl)sulfide bishexafluorophosphate, bis(4-(di(4-(2-hydroxyethoxy))phenylsulfonio)phenyl)sulfide bishexafluoroantimonate, bis(4-(di(4-(2-hydroxyethoxy))phenylsulfonio)phenyl)sulfide bistetrafluoroborate, bis(4-(di(4-(2-hydroxyethoxy))phenylsulfonio)phenyl)sulfide tetrakis(pentafluorophenyl)borate, tris(4-(4-acetylphenyl)thiophenyl)sulfonium tetrakis(pentafluorophenyl)borate, and the like. Of these, triarylsulfonium tetrakis(pentafluorophenyl)borate such as triphenylsulfonium tetrakis(pentafluorophenyl)borate is preferred.

[0021] Examples of the aromatic iodonium salt include diphenyliodonium hexafluorophosphate, diphenyliodonium hexafluoroantimonate, diphenyliodonium tetrafluoroborate, diphenyliodonium tetrakis(pentafluorophenyl)borate, bis(dodecylphenyl)iodonium hexafluorophosphate, bis(dodecylphenyl)iodonium hexafluoroantimonate, bis(dodecylphenyl)iodonium tetrafluoroborate, bis(dodecylphenyl)iodonium tetrakis(pentafluorophenyl)borate, 4-methylphenyl-4-(1-methylethyl)phenyliodonium hexafluorophosphate, 4-methylphenyl-4-(1-methylethyl)phenyliodonium hexafluoroantimonate, 4-methylphenyl-4-(1-methylethyl)phenyliodonium tetrafluoroborate, and 4-methylphenyl-4-(1-methylethyl)phenyliodonium tetrakis(pentafluorophenyl)borate.

[0022] Examples of the aromatic diazonium salt include phenyldiazonium hexafluorophosphate, phenyldiazonium hexafluoroantimonate, phenyldiazonium tetrafluoroborate, and phenyldiazonium tetrakis(pentafluorophenyl)borate.

[0023] Examples of the aromatic ammonium salt include 1-benzyl-2-cyanopyridinium hexafluorophosphate, 1-benzyl-2-cyanopyridinium hexafluoroantimonate, 1-benzyl-2-cyanopyridinium tetrafluoroborate, 1-benzyl-2-cyanopyridinium tetrakis(pentafluorophenyl)borate, 1-(naphthylmethyl)-2-cyanopyridinium hexafluorophosphate, 1-(naphthylmethyl)-2-cyanopyridinium hexafluoroantimonate, 1-(naphthylmethyl)-2-cyanopyridinium tetrafluoroborate, and 1-(naphthylmethyl)-2-cyanopyridinium tetrakis(pentafluorophenyl)borate.

[0024] Examples of the (2,4-cyclopentadiene-1-yl)((1-methylethyl)benzene)-Fe salt include (2,4-cyclopentadiene-1-yl)((1-methylethyl)benzene)-Fe(II) hexafluorophosphate, (2,4-cyclopentadiene-1-yl)((1-methylethyl)benzene)-Fe(II) hexafluoroantimonate, (2,4-cyclopentadiene-1-yl)((1-methylethyl)benzene)-Fe(II) tetrafluoroborate, and (2,4-cyclopentadiene-1-yl)((1-methylethyl)benzene)-Fe(II) tetrakis(pentafluorophenyl)borate.

[0025] Examples of the nonionic photoacid generating cationic photopolymerization initiator include nitrobenzyl esters, sulfonic acid derivatives, phosphoric acid esters, phenolsulfonic acid esters, diazonaphthoquinones, and N-hydroxyimide sulfonates.

[0026] Among the above-mentioned photocationic polymerization initiators, commercially available ones include, for example, photocationic polymerization initiators manufactured by Midori Chemical Industry Co., Ltd., photocationic polymerization initiators manufactured by Union Carbide Corporation, photocationic polymerization initiators manufactured by ADEKA Corporation, photocationic polymerization initiators manufactured by 3M Corporation, photocationic polymerization initiators manufactured by BASF Corporation, photocationic polymerization initiators manufactured by Solvay Corporation, and photocationic polymerization initiators manufactured by San-Apro Corporation. An example of the photocationic polymerization initiator manufactured by Midori Kagaku Co., Ltd. is DTS-200. Examples of the photocationic polymerization initiator manufactured by Union Carbide include UVI6990 and UVI6974. Examples of the photocationic polymerization initiator manufactured by ADEKA Corporation include SP-150 and SP-170. Examples of the photocationic polymerization initiator manufactured by 3M include FC-508 and FC-512. Examples of the cationic photopolymerization initiator manufactured by BASF include IRGACURE261 and IRGACURE290. Examples of the photocationic polymerization initiators manufactured by Solvay include PI2074. Examples of the photocationic polymerization initiators manufactured by San-Apro include CPI-100P, CPI-200K, and CPI-210S.

[0027] The polymerization initiators may be used alone or in combination of two or more kinds.

[0028] The content of the polymerization initiator is preferably 1 part by mass at the lower limit and 20 parts by mass at the upper limit with respect to 100 parts by mass of the curable resin. By the content of the polymerization initiator being within this range, the obtained curable resin composition has better curability and storage stability. The more preferred lower limit of the content of the polymerization initiator is 3 parts by mass, and the more preferred upper limit is 15 parts by mass.

[0029] From the viewpoint of light resistance, the curable resin composition of the present invention may further contain an ultraviolet absorber.

[0030] Examples of the ultraviolet absorber include 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-ethoxy-2'-ethyloxalic acid bisanilide, dimethyl succinate-1-(2-hydroxyethyl)-4-hydroxy-2,2,6,6-tetramethylpiperidine polycondensate, 2-(2'-hydroxy-4'-n-octoxyphenyl)benzotriazole, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-n-octoxybenzophenone, phenyl salicylate, pt-butylphenyl salicylate, and 2-ethylhexyl 2-cyano-3,3-diphenylacrylate.

[0031] The content of the ultraviolet absorbent is preferably 0.001 parts by mass at the lower limit and 5 parts by mass at the upper limit with respect to 100 parts by mass of the curable resin. By the content of the ultraviolet absorbent being within this range, the obtained curable resin composition has better light resistance. The more preferred lower limit of the content of the ultraviolet absorbent is 0.1 parts by mass, and the more preferred upper limit is 1 part by mass.

[0032] The curable resin composition of the present invention may further contain a leveling agent from the viewpoint of the flatness of the coating film.

[0033] Examples of the leveling agent include silicone-based leveling agents, fluorine-based leveling agents, and acrylic-based leveling agents.

[0034] The content of the leveling agent is preferably 0.01 parts by mass at the lower limit and 10 parts by mass at the upper limit with respect to 100 parts by mass of the curable resin. By the content of the leveling agent being within this range, the obtained curable resin composition has better coatability and flatness of the coating film. The more preferred lower limit of the content of the leveling agent is 0.03 parts by mass, and the more preferred upper limit is 1 part by mass.

[0035] From the viewpoint of coatability, the curable resin composition of the present invention may further contain a thixotropy-imparting agent.

[0036] Examples of the thixotropy-imparting agent include polysiloxane, polyacrylic, polyamide, polyvinyl alcohol, polyether ester, alkyl-modified cellulose, peptide, polypeptide, silica, and the like.

[0037] The content of the thixotropy-imparting agent is preferably 0.1 parts by mass at the lower limit and 5 parts by mass at the upper limit with respect to 100 parts by mass of the curable resin. By the content of the thixotropy-imparting agent being within this range, the obtained curable resin composition has better coatability. The more preferred lower limit of the content of the thixotropy-imparting agent is 1 part by mass, and the more preferred upper limit is 3 parts by mass.

[0038] Since the curable resin composition of the present invention has excellent low outgassing properties and does not require a solvent removal step, the solvent content is preferably 1 mass % or less, more preferably 0.1 mass % or less, and even more preferably 0.05 mass % or less, and it is particularly preferable that the composition does not contain a solvent.

[0039] Furthermore, the curable resin composition of the present invention may contain various known additives, such as dyes, curing retarders, reinforcing agents, viscosity modifiers, and antioxidants, as necessary.

[0040] The curable resin composition of the present invention has a viscosity measured at 25°C using an E-type viscometer of preferably 10 mPa·s lower limit and 50,000 mPa·s upper limit. When the viscosity is within this range, the resulting curable resin composition has excellent coatability. The more preferred lower limit of the viscosity is 20 mPa·s, and the more preferred upper limit is 10,000 mPa·s. The viscosity can be measured, for example, using a VISCOMETER TV-22 (manufactured by Toki Sangyo Co., Ltd.) as an E-type viscometer, with a No. 1 rotor at a rotation speed of 1 rpm or 10 rpm.

[0041] The curable resin composition of the present invention is cured by using a UV-LED at a wavelength of 365 nm and an illuminance of 100 mW / cm 2 The pencil hardness of the cured product obtained by irradiating the cured product with ultraviolet light for 30 seconds and then heating at 100°C for 30 minutes, as measured in accordance with JIS K 5600-5-4 (hereinafter also simply referred to as "pencil hardness of the cured product"), is preferably 4H or more. Since the pencil hardness of the cured product is 4H or more, the curable resin composition of the present invention can be suitably used as a hard coat agent for protecting and sealing optical semiconductor elements and the like. The pencil hardness of the cured product is more preferably 7H or more. The curable resin composition of the present invention can be cured by UV-LED at a wavelength of 365 nm and an illuminance of 100 mW / cm. 2The cured product obtained by irradiating the cured product with ultraviolet rays for 30 seconds and then heating at 100°C for 30 minutes is preferably exposed to an environment of 85°C and 85% RH for 24 hours in a reliability test, and then has a pencil hardness (hereinafter also referred to as "pencil hardness of the cured product after reliability test") measured according to JIS K 5600-5-4 of 4H or more. Since the cured product after the reliability test has a pencil hardness of 4H or more, the curable resin composition of the present invention can be suitably used as a hard coat agent for protective sealing of optical semiconductor elements and the like, even when exposed to a high-temperature and high-humidity environment. It is more preferable that the pencil hardness of the cured product after the reliability test is 7H or more. The pencils used to measure pencil hardness range from 6B to 10H in hardness. In addition, in this specification, a pencil hardness of "nH or more (n is an integer)" means that the pencil hardness is nH or is harder than the hardness that results in nH.

[0042] From the viewpoint of reliability when the curable resin composition of the present invention is used as a hard coating agent for protective encapsulation of optical semiconductor elements and the like, the difference between the pencil hardness of the cured product and the pencil hardness of the cured product after the reliability test is preferably 2 levels or less, more preferably 1 level or less, and most preferably 0 level, i.e., the pencil hardness of the cured product and the pencil hardness of the cured product after the reliability test are the same.

[0043] The curable resin composition of the present invention is cured by using a UV-LED at a wavelength of 365 nm and an illuminance of 100 mW / cm 2 The cured product obtained by irradiating the cured product with ultraviolet light for 30 seconds and then heating at 100°C for 30 minutes is preferably classified as 0 or 1 in an adhesion test by a cross-cut method in accordance with JIS K 5600-5-6 (hereinafter, also simply referred to as "adhesion classification of the cured product"). Since the adhesion classification of the cured product is 0 or 1, the curable resin composition of the present invention can be suitably used as a hard coat agent for protecting and sealing optical semiconductor elements and the like. It is most preferable that the adhesion classification of the cured product is 0. The curable resin composition of the present invention can be cured by UV-LED at a wavelength of 365 nm and an illuminance of 100 mW / cm. 2 The cured product obtained by irradiating the cured product with ultraviolet light for 30 seconds and then heating at 100°C for 30 minutes is preferably classified as 0 or 1 in an adhesion test by a cross-cut method according to JIS K 5600-5-6 after a reliability test in which the product is exposed to an environment of 85°C and 85% RH for 24 hours (hereinafter also referred to as "adhesion classification of the cured product after reliability test"). Since the adhesion classification of the cured product after the reliability test is 0 or 1, the curable resin composition of the present invention can be suitably used as a hard coat agent for protective sealing of optical semiconductor elements and the like, even when exposed to a high-temperature and high-humidity environment. It is most preferable that the adhesion classification of the cured product after the reliability test is 0.

[0044] The curable resin composition of the present invention can be used for hard coating agents, sealants for displays, microlenses, etc. In particular, it is suitably used for protecting and sealing optical semiconductor elements, etc. by forming a coating layer on the optical semiconductor elements, etc. as a hard coating agent, or by covering the optical semiconductor elements, etc. as a film. The present invention also includes a coating layer formed using the curable resin composition of the present invention.The present invention also includes a film formed using the curable resin composition of the present invention.

[0045] The coating layer of the present invention can be formed by applying the curable resin composition of the present invention onto a substrate such as an optical semiconductor element and then curing the composition. The film of the present invention can be formed by applying the curable resin composition of the present invention onto a release film or the like and then curing the composition.

[0046] Examples of the method for applying the curable resin composition of the present invention include a spin coating method, a bar coating method, and an inkjet method.

[0047] When the curable resin composition of the present invention contains the above-mentioned photopolymerization initiator as the above-mentioned polymerization initiator, the curable resin composition of the present invention can be easily cured by irradiation with light. The method for curing the curable resin composition of the present invention by light irradiation may be, for example, a method using a wavelength of 300 nm or more and 400 nm or less and a light irradiation speed of 300 mJ / cm. 2 More than 3000mJ / cm 2 Examples of the method include a method of irradiating light with the following integrated amount of light.

[0048] Examples of light sources for irradiating the curable resin composition of the present invention with light include UV-LEDs, low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, excimer lasers, chemical lamps, black light lamps, microwave-excited mercury lamps, metal halide lamps, sodium lamps, halogen lamps, xenon lamps, fluorescent lamps, sunlight, electron beam irradiation devices, etc. These light sources may be used alone or in combination of two or more. These light sources are appropriately selected in accordance with the absorption wavelength of the photopolymerization initiator.

[0049] Examples of the means for irradiating the curable resin composition of the present invention with light include simultaneous irradiation with various light sources, sequential irradiation with a time lag, and a combination of simultaneous irradiation and sequential irradiation. Any irradiation means may be used.

[0050] The curable resin composition of the present invention may be cured by heating after the above-mentioned light irradiation. Effect of the Invention

[0051] According to the present invention, it is possible to provide a curable resin composition capable of obtaining a cured product having excellent hardness and adhesion even when exposed to a high-temperature and high-humidity environment. In addition, according to the present invention, it is possible to provide a coating layer and a film formed using the curable resin composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0052] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0053] Example 2、 3, 6, Reference example 1、 4, 5, 7, 8, and Comparative Examples 1 to 6) According to the mixing ratios shown in Table 1, each material was mixed by stirring using a stirring mixer. 2、 3, 6, Reference example 1、 The curable resin compositions were prepared as Nos. 4, 5, 7, and 8, and Comparative Examples 1 to 6. Awatori Rentaro ARE-310 (manufactured by Thinky Corporation) was used as the stirring mixer.

[0054] <Evaluation> The following evaluations were carried out for each of the obtained curable resin compositions, and the results are shown in Table 1.

[0055] (Hardness and hardness retention of the cured product) Each of the obtained curable resin compositions was applied onto a glass substrate having a length of 5 cm, a width of 5 cm, and a thickness of 0.7 mm using a spin coater at 900 rpm for 20 seconds to obtain a coating film having a thickness of 10 μm. Then, a UV-LED was used to apply a 365 nm wavelength and 100 mW / cm illuminance. 2 After irradiation with ultraviolet light for 30 seconds, the curable resin composition was cured by heating at 100° C. for 30 minutes to obtain a test piece. The pencil hardness of the obtained test pieces was measured under a load of 750 g in accordance with JIS K 5600-5-4, and the hardness of the cured product was evaluated according to the following criteria: Pencils with hardness ranging from 6B to 10H were used. In addition, the obtained test pieces were subjected to a reliability test in which they were exposed to an environment of 85° C. and 85% RH for 24 hours, and then the pencil hardness was measured in the same manner to evaluate the hardness of the cured product after the reliability test. AA: Pencil hardness is 7H or higher A: When the pencil hardness is between 4H and 6H B: Pencil hardness was 3H or less In this specification, the pencil hardness "nH or less (n is an integer)" means that the pencil hardness is nH or is softer than nH. Furthermore, the hardness retention was evaluated according to the following criteria from the difference between the pencil hardness of the cured product (the pencil hardness of the cured product not subjected to the reliability test) and the pencil hardness of the cured product after the reliability test. AA: When the pencil hardness of the cured product is the same as that of the cured product after the reliability test (difference is 0 level) A: When the difference between the pencil hardness of the cured product and the pencil hardness of the cured product after the reliability test is 1 or 2 steps B: When the difference between the pencil hardness of the cured product and the pencil hardness of the cured product after the reliability test is 3 or more levels

[0056] (Adhesion to glass) Each of the obtained curable resin compositions was applied onto a glass substrate having a length of 5 cm, a width of 5 cm, and a thickness of 0.7 mm using a spin coater at 900 rpm for 20 seconds to obtain a coating film having a thickness of 10 μm. Then, a UV-LED was used to apply a 365 nm wavelength and 100 mW / cm illuminance. 2 After irradiation with ultraviolet light for 30 seconds, the curable resin composition was cured by heating at 100° C. for 30 minutes to obtain a test piece. The obtained test pieces were cut in a grid pattern using a cutter to provide test locations in accordance with JIS K 5600-5-6, and tape (manufactured by Nichiban Co., Ltd., "Cellotape (registered trademark) No. 405") was applied to the test locations, and then an adhesion test was performed using the cross-cut method in which the tape was peeled off. The cut interval was 1 cm, and the tape peel angle was 90°. The test pieces after the adhesion test were visually observed, and the adhesion to glass was evaluated according to the following criteria based on the classification in JIS K 5600-5-6 (adhesion classification). In addition, the obtained test pieces were subjected to a reliability test in which they were exposed to an environment of 85°C and 85% RH for 24 hours, and then an adhesion test was similarly performed by the cross-cut method to evaluate the adhesion to glass after the reliability test. AA: Adherence classification was 0 or 1 A: If the adhesion classification is 2 or 3 B: Adherence classification was 4 or 5

[0057] [Table 1] [Industrial Applicability]

[0058] According to the present invention, it is possible to provide a curable resin composition capable of obtaining a cured product having excellent hardness and adhesion even when exposed to a high-temperature and high-humidity environment. In addition, according to the present invention, it is possible to provide a coating layer and a film formed using the curable resin composition.

Claims

1. Contains a curable resin, a coupling agent, and a polymerization initiator; The curable resin includes a curable resin having four or more glycidyl groups in one molecule, The coupling agent includes a coupling agent having one glycidyl group in one molecule, the content of the coupling agent having one glycidyl group in one molecule is 20 parts by mass or more and 50 parts by mass or less relative to 100 parts by mass in total of the entire curable resin and the entire coupling agent, Used to form a coating layer or film A curable resin composition comprising:

2. A curable resin composition comprising a curable resin, a coupling agent, and a polymerization initiator, The curable resin includes a curable resin having two or more glycidyl groups in one molecule, The coupling agent includes a coupling agent having one glycidyl group in one molecule, the content of the coupling agent having one glycidyl group in one molecule is 20 parts by mass or more and 50 parts by mass or less relative to 100 parts by mass in total of the entire curable resin and the entire coupling agent, The curable resin composition was irradiated with a UV-LED at a wavelength of 365 nm and an illuminance of 100 mW / cm 2 and then heating at 100°C for 30 minutes to obtain a cured product, which is then subjected to a reliability test in which the product is exposed to an environment of 85°C and 85% RH for 24 hours. The pencil hardness measured in accordance with JIS K 5600-5-4 is 4H or more. The curable resin composition was irradiated with a UV-LED at a wavelength of 365 nm and an illuminance of 100 mW / cm 2 After irradiating the cured product with ultraviolet light of 100°C for 30 seconds and then heating at 100°C for 30 minutes, a reliability test was conducted in which the product was exposed to an environment of 85°C and 85% RH for 24 hours. After that, the adhesion test using the cross-cut method according to JIS K 5600-5-6 gave a classification of 0 or 1. A curable resin composition comprising:

3. The curable resin composition according to claim 1 , wherein the polymerization initiator includes a photopolymerization initiator.

4. A coating layer formed using the curable resin composition according to claim 1 or 2.

5. A film formed using the curable resin composition according to claim 1 or 2.

Citation Information

Patent Citations

  • Photoocurable composition for bonding glass

    JP1978120799A

  • Hard coating agent, sealing composition, laminate, and light-emitting device

    JP2016001657A

  • Curable resin composition and cured product

    JP2022153475A

  • Curable resin composition, cured product, rugged structure and method for producing rugged structure

    WO2018230725A1